Effects of active versus passive recovery on thermoregulatory strain and performance in intermittent-sprint exercise - Bishop, D.; Ruch, N.; Paun, V. (Medicine & Science in Sports & Exercise, 2007)
Purpose: Team sports contain high-intensity sprints separated by active recovery (AR) and passive recovery (PR). The beneficial effects of AR on repeated-sprint performance, for short exercise duration, in thermoneutral environments, are well known. However, team sports are often performed in hot environments for prolonged periods. Therefore, the aim was to investigate the thermal strain of AR versus PR during prolonged, intermittent-sprint exercise.